ABCB1 genetic variants in leukemias: current insights into treatment outcomes - Ankathil, Ravindran (Dove Medical Press, 2017)
Despite improvements in treatment of different types of leukemia, not all patients respond optimally for a particular treatment. Some treatments will work better for some, while being harmful or ineffective for others. This is due to genetic variation in the form of singlenucleotide polymorphisms (SNPs) that affect gene expression or function and cause inherited interindividual differences in the metabolism and disposition of drugs. Drug transporters are one of the determinants governing the pharmacokinetic profile of chemotherapeutic drugs. The ABCB1 transporter gene transports a wide range of drugs, including drugs used in leukemia treatment. Polymorphisms in the ABCB1 gene do affect intrinsic resistance and pharmacokinetics of several drugs used in leukemia treatment protocols and thereby affect the efficacy of treatment and event-free survival. This review focuses on the impact of three commonly occurring SNPs (1236C>T, 2677G>T/A, and 3435C>T) of ABCB1 on treatment response of various types of leukemia. From the literature available, some of the genotypes and haplotypes of these SNPs have been found to be potential determinants of interindividual variability in drug disposition and pharmacologic response in different types of leukemia. However, due to inconsistencies in the results observed across the studies, additional studies, considering novel genomic methodologies, comprehensive definition of clinical phenotypes, adequate sample size, and uniformity in all the confounding factors, are warranted.